Creating Entrepreneurial Possibilities in Library and Information Science: Remedying the Narrative of Unemployment - OKWU , Emmanuel; OPURUM , Augustine Chineme; EKE, Prince Chibuzor (Covenant Journal of Entrepreneurship, 2024)
The paper explores creating entrepreneurial possibilities in Library and Information Science: remedying the unemployment narrative. It portrayed entrepreneurship as the engine house for economic advancement as it plays a vital role in the growth and development of society. It is a treasured instrument for creating wealth, jobs, poverty alleviation, and overall societal progress. There is an outright recognition that information is the chief commodity of the contemporary age and thus saleable. Librarians who market and approach information services with this perspective will unquestionably sell. It captured leadership and information literacy, among others, as skills required of entrepreneurs to function optimally. The entrepreneurial opportunities for remedying the issue of unemployment were excellently highlighted, including information brokerage, database brokerage, information system consultancy, and information organisation service, among others. The paper held that Library and Information Science professionals who venture into entrepreneurship often experience a lack of requisite information literacy skills, a lack of entrepreneurial spirit, an absence of technological literacy, access to market channels, and poor patronage as challenges. Therefore, it was recommended, among others, that library schools deliberately inculcate the culture of entrepreneurship in undergraduates as a remedy to the issue of unemployment among graduates.